Developing Familiarity in a New Duo: Rehearsal Talk and Performance Cues - Ginsborg, Jane; Bennett, Dawn (Frontiers in Psychology, 2021)
Context and aims: Social and cognitive processes underlying individual musicians’ and duo performers’ preparation for performance have been explored using longitudinal case studies. Social processes can be inferred from rehearsal talk and recent studies have focused on its content and nature. Cognitive processes can be inferred from score annotations representing musicians’ thoughts while practicing, rehearsing (rehearsal features), and playing or singing from memory (performance cues). We report three studies: 1) of rehearsal talk; 2) of rehearsal features and thoughts while performing; and 3) a triangulation of the two kinds of data to gauge the potential for rehearsal talk to predict the use of performance cues. Methods: A singer and viola player formed a new duo to prepare two songs, new to them both, for two performances on the same day and a third performance ten months later. Their practice and rehearsal sessions, over the course of seven days, were recorded and transcribed. The musicians annotated copies of the scores after rehearsing and after each performance. Each musician performed one of the two songs from memory. First, verbal data were coded and analyzed using two frameworks for categorizing socio-emotional interactions and musical dimensions respectively. Second, their annotations were categorized and compared, and finally the frameworks were combined so that correlations between rehearsal talk and performance cues could be calculated. Results: The musicians’ verbal interactions were positive and task-related; significant changes over time were observed only in the extent to which they showed solidarity towards each other. Analysis of their annotations illustrates similarities and differences between their attention to specific features of the music while rehearsing and performing, particularly from memory. Rehearsal talk predicted performance cues in the third performance, but not the first or second. Conclusion: Musicians’ talk cannot be assumed to reflect musicians’ actions. The study of musicians’ verbal interactions may be less useful for determining cognitive than social processes underlying preparation for performance. Nevertheless, the study provides a detailed snapshot of musicians’ “real world” preparation for performance, highlighting the role of spontaneity in performance, and underlining differences between what happens in the studio and what can happen on stage.